Salt vats where water is evaporated by solar heat, Syracuse, New York (Underwood & Underwood)
View of salt vats where water is evaporated by means of solar heat at an unknown facility in Syracuse, New York. This photograph is one of a set of six stereographs detailing the mining and production of salt.
Keywords: Employees; Manufacturing industries; Salt industry and trade; Salt mines and mining